2013
DOI: 10.1215/15314200-2266432
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Close Reading Skills in a Large Lecture Course

Abstract: The faculty and graduate student authors of this article taught English Literature before 1660 -"Beowulf to Milton" -in the fall 2010 semester to about 120 students at the University of Michigan. Students in this course are supposed to learn to read literature written in unfamiliar genres and verse forms, originally composed in several languages (Old English, Anglo-Norman, Middle English, Early Modern English) across a historical span of over 900 years. This wide historical range makes the course challenging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Reading for complexity, as I articulate this shared learning outcome, requires the navigation of diverse perspectives, the exploration of many possible interpretations, and the active construction of meaning with (not merely of ) the text. This learning outcome is consistent with what research in SoTL and writing in the disciplines (WID) has identified as the characterizing features of disciplinary reading in literary studies (Chick et al, 2009;Tinkle et al, 2013;Wilder, 2012;Wolfe & Wilder, 2016). This includes the analogous relation literary scholars draw between literature and the world through the shared traits of complexity, ambiguity, multiplicity, and difficulty (Bruns, 2011;Linkon, 2011;Rosenblatt, 1995;Salvatori & Donahue, 2005;Zunshine, 2006).…”
Section: Identifying "Reading For Complexity" As a Disciplinary Learn...supporting
confidence: 85%
“…Reading for complexity, as I articulate this shared learning outcome, requires the navigation of diverse perspectives, the exploration of many possible interpretations, and the active construction of meaning with (not merely of ) the text. This learning outcome is consistent with what research in SoTL and writing in the disciplines (WID) has identified as the characterizing features of disciplinary reading in literary studies (Chick et al, 2009;Tinkle et al, 2013;Wilder, 2012;Wolfe & Wilder, 2016). This includes the analogous relation literary scholars draw between literature and the world through the shared traits of complexity, ambiguity, multiplicity, and difficulty (Bruns, 2011;Linkon, 2011;Rosenblatt, 1995;Salvatori & Donahue, 2005;Zunshine, 2006).…”
Section: Identifying "Reading For Complexity" As a Disciplinary Learn...supporting
confidence: 85%
“…However, TPS with multiple-choice questions is certainly not limited to questions with a single best answer, in STEM or other disciplines (Bruff 2009;Tinkle et al 2013). For example, in the Humanities one can practice "close reading" and critical thinking during class, even in large lectures, by providing students with a text passage or work of art and multiple-choice questions about how best to interpret or analyze it.…”
Section: Discussionmentioning
confidence: 99%
“…During each lecture session following a lab, we implemented an active learning technique known as TPS that has been used in many areas of education, including fields as disparate as Biology (Smith et al 2009), Computer Science (Porter et al 2011), and Comparative Literature (Bruff 2009;Tinkle et al 2013). TPS combines an individual activity ("Think") with a low-stakes peer discussion ("Pair"), followed by a whole-class debrief ("Share"), encouraging all students to engage cognitively and summarize a concept in their own words (Lyman 1987).…”
Section: Introductionmentioning
confidence: 99%
“…As a secondary lens, SPN can be applied to studies that look at large institutional endeavors or to classroom-specific analyses. For instance, a thoughtful exploration of large classroom dynamics and the importance of experimenting in this type of setting is explored by Tinkle, Atias, McAdams, and Zukerman (2013). In "Teaching Close Reading Skills in a Large Lecture Course," the authors do not explicitly state that they are engaged in SPN, but they draw from the SPN practices.…”
Section: Analysis Of Spn Examplesmentioning
confidence: 99%